PART I. DECREPITATION AND DEGASSING BEHAVIOUR OF QUARTZ UP TO 1560°C: ANALYSIS OF NOBLE GASES AND HALOGENS IN COMPLEX FLUID INCLUSION ASSEMBLAGES - Kendrick M.A.; Phillips D.; Miller J.M. (My University, 2006)
Stepped heating and crushing experiments have been used to investigate the noble gas and halogen degassing behaviour of quartz in detail. Samples with diverse character were selected from the Eloise and Osborne, Iron Oxide Copper Gold (IOCG) ore deposits, and the Railway Fault, 13 km south of the Mt Isa Mine, in the Proterozoic Mt Isa Inlier of northeast Australia. Quartz has been shown to have a bimodal degassing profile. The first degassing mode at temperatures of <700 °C is caused by thermally induced mechanical decrepitation of fluid inclusions. Changes in the Br/Cl, I/Cl, Ar/Cl and 40Ar/36Ar composition of gas released at different temperatures up to 700 °C can be related to the decrepitation of different types of fluid inclusion observed by microthermometry. These variations with temperature permit deconvolution of the complex fluid inclusion assemblages associated with the IOCG samples; the ultra high salinity, multi solid (MS) and liquid-vapour-daughter (LVD) fluid inclusions, with a predominantly primary origin, decrepitate at higher temperatures than lower salinity liquid-vapour (LV) and monophase (M) fluid inclusions that have a predominantly secondary origin. Three of the IOCG samples have primary MS and LVD fluid inclusions characterized by molar Br/Cl values of between 0.25 ? 10-3 and 0.66 ? 10-3, I/Cl between 0.37 ? 10-6 and 5.0 ? 10-6, 40Ar/36Ar values of <1000 and low 36Ar concentrations of 0.7-1.0 ? 10-6 cm3 cm-3H2O. These low values are most easily explained by the involvement of halite dissolution water in IOCG genesis. One of the IOCG samples has Br/Cl of 1.3-2.0 ? 10-3 and I/Cl of 10 ? 10-6, similar to juvenile magmatic fluids in Phanerozoic Porphyry Copper Deposits. This sample also has a higher 36Ar concentration of 3.5 ? 10-6 cm3 cm-3H2O and a slightly elevated 40Ar/36Ar of 2236. Step heating reveals limited and non-systematic variation within the more homogenous population of LV fluid inclusions from the Railway Fault. The samples have mean values of 8.1 ? 10-3 for Br/Cl; 9.4-12 ? 10-6 for I/Cl; <2000 for 40Ar/36Ar; and 4.7-4.8 ? 10-6 cm3 cm-3H2O for 36Ar concentration. The Br/Cl values are similar to those previously reported for basinal brines present in silicic alteration at the Mt Isa Mine and the additional data can be explained by interaction of such a bittern brine with fine grained sedimentary rocks in the sub-surface. The second mode of quartz degassing occurs between 1200 and 1450 °C and releases a greater volume of gas than the first degassing mode. Several lines of evidence, including microscope observations, indicate that the gas released at high temperature is also from the fluid inclusion reservoir. However, its release may be triggered by a metastable phase transition of quartz (?1200 °C) and caution is required in interpretation of the fluid compositions obtained at these temperatures. The data provide an improved understanding of fluid inclusion decrepitation behaviour that is different to that obtained in lower temperatures experiments designed by other workers to investigate H-isotope fractionation. ? 2006 Elsevier Inc. All rights reserved.
Keywords: DEGASSING; FLUID INCLUSION; HALOGEN; NOBLE GAS; QUARTZ; Proterozoic; Докембрий::Протерозой; Precambrian::Proterozoic